S100A8/A9 in herpes zoster neuralgia: molecular mechanisms and therapeutic perspectives - Jiang, Dongzhi; Zhang, Ziyuan; Ren, Fei; Sun, Wenqin (Frontiers in Immunology, 2025)
Herpes zoster (HZ), a neurological disorder resulting from varicella-zoster virus (VZV) reactivation, presents significant clinical challenges, particularly in the development of postherpetic neuralgia (PHN). This comprehensive review elucidates the pivotal role of S100A8/A9, a damage-associated molecular pattern (DAMP) molecule, in the pathogenesis of chronic pain transition. By systematically analyzing molecular mechanisms, we provide unprecedented insights into the complex neuroimmune interactions underlying HZ-associated neuropathic pain. Our investigation reveals S100A8/A9’s critical function in modulating neuroinflammatory processes through TLR4/TNF signaling pathways, demonstrating its potential as a sophisticated therapeutic target. The protein complex orchestrates intricate cellular communications, fundamentally disrupting neuronal homeostasis and contributing to pain chronification. Emerging technological platforms, including single-cell sequencing and multi-omics analysis, have substantially enhanced our understanding of these molecular dynamics. The review critically examines current therapeutic limitations and proposes innovative research directions. By integrating molecular, cellular, and clinical perspectives, we highlight the urgent need for personalized intervention strategies that address the multifaceted mechanisms of HZ-induced neuropathic pain. Our findings underscore S100A8/A9’s significance as a promising biomarker and potential therapeutic intervention in neurological disorders.